Code-Switching in Interactions between Teacher and Students with Different Levels of Language Proficiencies - Anggarsari, Rian Hardika; Faridi, Abdurrachman; Rukmini, Dwi (Universitas Negeri Semarang, 2021)
In an English teaching and learning process, teachers and students have interactions that occupy the students’ first language. It can be related to the existence of code-switching. It can help them fill in the gap which occurs during a conversation. It can improve the quality of teaching and learning. This study focuses on the analysis of code-switching in the interactions between the teacher and the students with different levels of language proficiency. This study examines how the teacher produced code-switching, the students’ responses towards the teacher’s code-switching, and the teacher’s roles code-switching. This study employed qualitative research. The instruments used for collecting data were audio-video recording, test, interview, and questionnaire. Findings of the study revealed that (1) the teacher used three types of code-switching to the students with different levels of language proficiency and the function of repetitive was the most frequent function found in the interactions, (2) the students responded to the teacher’s code-switching by using English, Indonesian language or code-switching, and (3) the roles of teacher as a controller and a director have the crucial use in the interactions. Hopefully, further studies can explore code-switching deeply in the interactions between teachers and students with different language proficiency levels in instructional settings.